Synthesis of Hyperbranched Polymer Using Slow Monomer Addition Method - Toshifumi Satoh (International Journal of Polymer Science)
This paper details the synthesis of a well-defined hyperbranched polymer using a slow monomer addition method. The polymerization under slow monomer addition conditions results in a very low monomer concentration actually present in the reaction mixture, and the exclusive reaction of the monomer with the growing polyfunctional macromolecules occurs, resulting in a high molecular weight and a high degree of branching value. Thus, the slow monomer addition is a versatile and preferential method for the controlled synthesis of a well-defined hyperbranched polymer with both a high molecular weight and a high degree of branching value.